2019
DOI: 10.1021/acsbiomaterials.9b01486
|View full text |Cite|
|
Sign up to set email alerts
|

Heparin-Encapsulated Metered-Dose Topical “Nano-Spray Gel” Liposomal Formulation Ensures Rapid On-Site Management of Frostbite Injury by Inflammatory Cytokines Scavenging

Abstract: The critical time window between the incidence of frostbite injury and the initiation of treatment in remote snowbound areas is a determining factor for an effective therapeutic response. It is an emergency condition and challenging to treat due to the poor vascularity of affected body parts, and it requires immediate action. In addition to cold trauma-induced tissue damage, the inflammatory mediators majorly contribute to pathologic aggravations. We have designed and evaluated a topical “nano-spray gel (NSG)”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…61,62 An initial rapid release of HP followed by a more sustained delivery is most suitable for the treatment of urgent clinical situations, such as vascular surgery, frostbite, dialysis, etc. 37,43,63 Thus, the development of HP delivery systems with fast responsive rate have attracted signicant attention. [64][65][66] The here prepared HP@MOF composites show release proles that are relevant for urgent medical treatments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…61,62 An initial rapid release of HP followed by a more sustained delivery is most suitable for the treatment of urgent clinical situations, such as vascular surgery, frostbite, dialysis, etc. 37,43,63 Thus, the development of HP delivery systems with fast responsive rate have attracted signicant attention. [64][65][66] The here prepared HP@MOF composites show release proles that are relevant for urgent medical treatments.…”
Section: Resultsmentioning
confidence: 99%
“…[64][65][66] The here prepared HP@MOF composites show release proles that are relevant for urgent medical treatments. 37,43,63 To test possible alteration in the biotherapeutic properties of HP due the encapsulation and recovery processes, we used a chromogenic anti-IIa assay to evaluate the anticoagulant activity of heparin before and aer being encapsulated within the three different MOFs (see ESI † for details). The collected data reveals that the HP released from ZIF-8 retains z98% of its initial activity, whereas the HP released from ZIF-90 and MAF-7 retains z95% and z97% activity, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescent confocal micrographs showed that fibroblasts exposed to the HLp (green fluorescence) for 3 h accumulated liposomes (in significant numbers) inside the cytoplasm of the cells (Figure 18B). No significant difference in cellular accumulation was observed between HLp and BLp [181]. HLp exhibited significant healing of a wound in vitro (scratch assay, fibroblast cells) and in vivo (wound healing in Sprague-Dawley rats) at a low dose.…”
Section: Light (Fluorescence and Confocal) Microscopy Techniquesmentioning
confidence: 84%
“…In skin wound condition a precise there wound appears after exposure to validated wound model, but in case of cold-injury the diameter of affected area is directly proportional to the cytokine response and individual's body pathophysiological response, thus it becomes necessary to carry out morphometric analysis as a routine basis to assess the changes in the received treatment groups and control groups. This analysis was carried out by the method described by Vaghasiya et al, (2019) where routine measurement of the frostbitten area was done with the help of Vernier caliper until complete healing of the cold-injured area. Percentage area (contracted wound) is calculated by the formula given below:…”
Section: Morphometric Analysis Of Frostbitten Wound Areamentioning
confidence: 99%